CE-39 Lupus in ST. lucia. (31st August 2016) - King, Amanda
Abstract : Background: Systemic lupus erythematosus is a chronic, systemic autoimmune disease of unknown cause. It is known to be more prevalent in Afro-Caribbean populations than in Caucasian, however there is little research on this population in the Caribbean. The most recent is "SLE in an African Caribbean population: Incidence, Clinical manifestations, and survival in the Barbados National lupus registry". 1 There is data from Martinique from 1990–1999 2 and from Curacao 1980–1989. 3 The 5 YSR ranged significantly from 60.1% in Curacao to 79.9% in Barbados and 96.4% in Martinique. The population of St. Lucia is 166526 (2010 census) and is of a similar ethnicity to Barbados and Martinique. There is one rheumatologist in St. Lucia. A study of her 131 private patients from 1995–2011 demonstrated a 5 YSR of 97%. 4 A national study is therefore required. Materials and methods: Patient information will be gathered from the rheumatologist's private clinic as well as from the public health centres and hospitals and from private practitioners and the public. The Ministry of health has agreed to set up a national registry and the rheumatologist is doing "lupus diagnosis and management" training of District Medical officers and Family nurse practitioners (and pharmacists etc.) in June 2016 after which 4 dedicated health practitioners will be apprenticed to her in the public clinic every month. There will be collaboration with the local arthritis and lupus support group and the media will be used to invite lupus patients to register. The rheumatology team will confirm the diagnosis satisfying ACR 1997 or SLICC) and enter data which will be analysed. Results: Preliminary results from the private patient cohort showed 92% Afro-Caribbean, 131 patients- 123 female, 8 male. Mean age- female 31, male 34. Incidence 6.5 per 100 000. Renal involvement 47%, renal failure 6.1%. Osteoporosis 29%. Conclusions: Lupus epidemiology is similar to Martinique and Barbados, with preliminary findings suggesting a relatively favourable prognosis. Renal failure remains the most common serious complication. Osteoporosis is frequent (on calcaneal ultrasound) and requires further study with an aim of better prevention and management. References: Flower C, Hennis A, Hambleton IR, Nicholson G, Liang MH, Barbados national lupus registry group. Systemic lupus erythematosus in an African Caribbean Population: Incidence, Clinical Manifestations, and Survival in the Barbados National lupus Registry. Arthritis Care and research 2012; 64 (8);1, 151–1, 158 Deligny C, Thomas L, Dubreuil F, Theodose C, Garsaud AM, Numeric P, et al . Systemic lupus erythematosus in Martinique: an epidemiologic study. Rev Med Interne 2002;23 :21–9 Nossent JC. Systemic lupus erythematosus on the Caribbean Island of Curacao: an epidemiological investigation. Ann Rheum Dis 1992;51:1197–1201. King A. SLE in St. Lucia- in private practice. Poster presentation Scottish society for rheumatology, 2013